3D‐Printable Antimicrobial Composite Resins. (9th October 2015) - Yue, Jun; Zhao, Pei; Gerasimov, Jennifer Y.; van de Lagemaat, Marieke; Grotenhuis, Arjen; Rustema‐Abbing, Minie; van der Mei, Henny C.; Busscher, Henk J.; Herrmann, Andreas; Ren, Yijin
Abstract : 3D printing is seen as a game‐changing manufacturing process in many domains, including general medicine and dentistry, but the integration of more complex functions into 3D‐printed materials remains lacking. Here, it is expanded on the repertoire of 3D‐printable materials to include antimicrobial polymer resins, which are essential for development of medical devices due to the high incidence of biomaterial‐associated infections. Monomers containing antimicrobial, positively charged quaternary ammonium groups with an appended alkyl chain are either directly copolymerized with conventional diurethanedimethacrylate/glycerol dimethacrylate (UDMA/GDMA) resin components by photocuring or prepolymerized as a linear chain for incorporation into a semi‐interpenetrating polymer network by light‐induced polymerization. For both strategies, dental 3D‐printed objects fabricated by a stereolithography process kill bacteria on contact when positively charged quaternary ammonium groups are incorporated into the photocurable UDMA/GDMA resins. Leaching of quaternary ammonium monomers copolymerized with UDMA/GDMA resins is limited and without biological consequences within 4–6 d, while biological consequences could be confined to 1 d when prepolymerized quaternary ammonium group containing chains are incorporated in a semi‐interpenetrating polymer network. Routine clinical handling and mechanical properties of the pristine polymer matrix are maintained upon incorporation of quaternary ammonium groups, qualifying the antimicrobially functionalized, 3D‐printable composite resins for clinical use. Abstract : Development of 3D printable, bacterial contact‐killing resins is acheived by incorporating positively charged compounds into the stereolithography‐compatible composite resins. Complex geometries of oral appliances bearing antimicrobial functions have been successfully printed and the mechanical properties of 3D printed objects are almost identical to conventionally photocured polymer samples, which implies potential applications in clinical use.